아질산성질소 측정용 FIA의 제작 및 응용에 관한 연구(광주광역시 광주천 시료를 대상으로) - 이재성; 박완철; 이수원; 김용준 (한국물환경학회, 2002)
In this study, home-made detection system by means of noble FIA is introduced on the measurement of toxic nitrite in the water samples collected from the area of Kwangju. As the standard calibration between 30 to 1000 ppb, the linearity has been shown more than 0.9999 as the correlation coefficient(R2) with the detection limit 1.5 ppb(S/N>2). The distribution of sample concentration was monitored as N.D. - 123 ppb which is wide span of concentrations in field water samples. The low level of nitrite is hardly detectable with other expensive sophisticated instruments including ion chromatography. Whereas the result of high concentration brings forth the necessity monitoring constantly our precious water resources. Successfully, the FIA system has played a very important role detecting wide span of nitrite in water sample. This technique can be adopted for controlling our environment in the near future.